Relationships between childhood trauma and mental health during the COVID-19 pandemic: a network analysis - Xia, Jinjin; Zhu, Lin; Huang, Huayun; Fan, Pengfei; Zhou, Meifeng; Cai, Xin-lu; He, Hui (Frontiers in Psychiatry, 2023)
Background Childhood trauma has been found to have an important impact on mental health. However, little is known regarding the intercorrelations between childhood trauma and mental health during the COVID-19 pandemic. This study aimed to investigate such complex interplay between childhood trauma, depression, anxiety, post-traumatic stress level during the COVID-19 pandemic, and fear of COVID-19 using network analysis. Methods A total of 1,247 college students were recruited and were asked to complete a series of questionnaires, including the Childhood Trauma Questionnaire, Patient Health Questionnaire, Generalized Anxiety Disorder Scale, Post-traumatic Stress Checklist—Civilian version, and Fear of COVID-19 Scale. The Gaussian graphical model with the scores of the questionnaires as nodes was estimated. The partial correlations between nodes were calculated as edges. Moreover, network comparison tests were conducted to compare the network patterns between participants with high levels of childhood trauma and low levels of childhood trauma. Results Childhood trauma was found to be connected to depression, anxiety, and post-traumatic stress level. The node of childhood trauma exhibited the strongest strength and the highest expected influence in the network. Participants with high levels of childhood trauma and participants with low levels of childhood trauma showed comparable network structure and global strength. Conclusion Our findings revealed a complex network pattern between childhood trauma and different mental health problems, indicating that childhood trauma might be a risk factor for mental health during the COVID-19 pandemic.